Design and analysis of the airfield lighting system (ALS) precision approach lighting system (PALS) on runway 14 Kertajati International Airport Majalengka - Aep Ma'shum Nurzaman (PT Pustaka Intelektual Sutajaya, 2025)
This study analyzed the design and implementation of the Precision Approach Lighting System (PALS) for Runway 14 at Kertajati International Airport, Majalengka. A qualitative case study approach was employed, combining field measurements, semi-structured interviews with airport operators and technicians, and document analysis based on ICAO Annex 14 Volume I and Indonesian regulation KP 326/2019. Field measurements determined precise lamp positions using theodolite equipment across 30 barrettes at 30-meter intervals, spanning 900 meters. Ground elevation assessments revealed variations from 0.0m to 5.75m, necessitating customized pole configurations ranging from 2.1m to 4.6m. Electrical system calculations determined a 25 KVA Constant Current Regulator (CCR) capacity with 7/8 tapping configuration, optimizing circuit loads at 74.42% and 77.48%. Primary cable lengths of 5,259m and 5,134m were calculated with 16mm² cross-sectional area for adequate power distribution. The integration of PALS with existing Instrument Landing System (ILS) enabled Category I precision approach capability, significantly enhancing aviation safety during low-visibility conditions. The design fully complied with international standards and supported Kertajati's operational capacity enhancement from 8 to 300 daily aircraft movements, establishing comprehensive all-weather operational capability.